Age‐Adjusted Glycated Albumin at Diagnosis is more Correlated with the Product of Age and Plasma Glucose than Plasma Glucose Alone in Patients with Neonatal Diabetes Mellitus. Issue 6 (28th April 2016) - Furuya, Akiko; Suzuki, Shigeru; Oshima, Miho; Amamiya, Satoshi; Nakao, Atsushi; Araki, Mariko; Mizutani, Kayo; Hayano, Satoshi; Ushijima, Katsumi; Imamoto, Aya; Nagano, Nobuhiko; Urakami, Tatsuhiko; et al.
Abstract : Background: We previously showed that glycated albumin (GA) is a useful glycemic control indicator in patients with neonatal diabetes mellitus (NDM), and that age‐adjusted GA (Aa‐GA) can reflect more accurately glycemic control status. Here, we investigated whether the age at diagnosis influences Aa‐GA at diagnosis of NDM. Methods: Eight patients with NDM whose GA was measured at diagnosis (age at diagnosis: 39 ± 18 days; GA: 31.3 ± 7.6%; Aa‐GA: 47.1 ± 10.3%; plasma glucose: 525 ± 194 mg/dl) were included. Aa‐GA was calculated as follows: Aa‐GA = GA × 14.0/[1.77 × log‐age (days) + 6.65]. Correlations of GA or Aa‐GA at diagnosis with its logarithmically transformed age in days (log‐age), plasma glucose, and their product were investigated. Results: GA at diagnosis was not significantly correlated with log‐age or plasma glucose. On the other hand, Aa‐GA at diagnosis was significantly positively correlated with plasma glucose ( R = 0.75, P = 0.031) and was more strongly positively correlated with the product of plasma glucose and log‐age ( R = 0.82, P = 0.012) although it was not correlated with log‐age. Conclusion: Aa‐GA at diagnosis is influenced by both age in days and plasma glucose. This finding is likely to show the aspect that age in days is almost equal to diabetes duration because glycemic control indicators including GA reflect the weighted mean of plasma glucose.